The Impact of the Dimensions of Strategic Foresight in Achieving the Organizational Brilliance of Banks/ Applied Research in a Number of Iraqi Private Commercial Banks - Hadeel Tareq Ali; Dr. Baydaa Sattar Lafta (Migration Letters, 2023)
The research aims to shed light on the dimensions of strategic foresight, namely environmental survey, future vision, scenarios, and restructuring, and measure their impact on achieving organizational brilliance in banks. Organizational brilliance is represented by leadership brilliance, service and innovation brilliance, knowledge brilliance, and employee brilliance. The research was conducted in several private Iraqi commercial banks, including Baghdad Bank, Iraqi Investment Bank, Iraqi Middle East Investment Bank, Business Bay Bank, Ashur International Investment Bank, Al-Mansour Investment Bank, and Across Iraq Investment Bank. The research adopted a descriptive analytical approach, utilizing a questionnaire as the main data collection tool. The statistical program used for data analysis was SPSS version 28. The research collected data from a sample of 165 officials across different job levels, including senior management, middle management, and executive management. This sample represents 60% of the total community of 277 officials. Various statistical methods were employed in the analysis, including weighted arithmetic mean, standard deviation, coefficient of variation, corrected interpretation coefficient AR2, analysis of variance (ANOVA), regression coefficient, and F-test. The key findings of the research indicate that there is an average level of interest among surveyed banks regarding the concept of strategic foresight. Moreover, the research highlights the positive impact of strategic foresight on achieving organizational brilliance. Additionally, significant differences were observed in the responses of the sample according to the surveyed banks.